Legal Certainty and Justice in Trademark Protection: A Comparative Analysis of the First-to-File System in Indonesia and the First-to-Use System in Malaysia - Nada Salshabilla Putri Hendrawan; Christian Andersen (Riviera Publishing, 2025)
This article examines the gap between das sein—the law as it operates in practice—and das sollen—the law as it ought to function—in the protection of trademarks in Indonesia and Malaysia, with particular emphasis on the legal treatment of well-known marks. By comparing Indonesia’s first-to-file framework to Malaysia’s first-to-use approach, this study highlights how Indonesia’s emphasis on strict registration creates certainty at the normative level but often fails to deliver substantive fairness in practice. In Indonesia, the reliance on registration as the sole basis for rights has resulted in recurring disputes involving well-known marks, such as Pierre Cardin and Starbucks, where opportunistic filings expose the limitations of the existing safeguards. Although statutory provisions prohibit bad-faith registration, practical enforcement remains inconsistent, leaving owners of established and globally recognized brands vulnerable. Malaysia, meanwhile, offers a more balanced structure by allowing prior use to take precedence over mere formal registration. This approach strengthens the position of rightful owners—especially proprietors of well-known marks whose reputation often precedes administrative filings—and equips them with legal avenues such as opposition proceedings, revocation, and passing off. The comparison reveals that Indonesia’s current regime still falls short of harmonizing legal certainty with fairness, as the protection afforded to well-known marks remains constrained by procedural rigidity. Enhancing the role of good-faith principles and formally recognizing prior use would bridge the gap between das sein and das sollen and foster a more just and reliable trademark system for both domestic and international stakeholders.